PENENTUAN HARGA POKOK PRODUKSI BATIK TULIS MENGGUNAKAN ACTIVITY BASED COSTING (ABC) : STUDI KASUS DI BATIK TOBAL PEKALONGAN - Ayu Ningtyas, Jilma Dewi; D. S., Bayu Wirawan (BAPPEDA Kota Pekalongan, 2019)
The purpose of this study is to produce a calculation of the cost of batik production based on activity based costing. The object of research is the cost of production cost in making batik in Tobal Batik in Pekalongan. For the subject of this study were written batik products from Batik Tobal Pekalongan business which is located at Jl. Teratai No. 24, Klego, Pekalongan Timur, Pekalongan City, Central Java. This type of research is qualitative by studying more in calculations with the activity based costing system in determining the cost of production in the business of Tobal batik. Data collection method uses observation, interview and documentation techniques. The data analysis method uses descriptive analysis by using the two-stage activity based costing system based on this research. It can be concluded that the determination of the cost of batik production in Batik Tobal by calculating the activity based costing system is Rp. 25,695,667, for the number of units produced 100 meters so the cost of producing batik per meter is IDR 256,957.